2021
DOI: 10.21107/ijseit.v6i1.12475
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Public e-Procurement to Sustainable Development Goals in Indonesia: Systematic Literature Review

Abstract: The Sustainable Development Goals have become the UN's global goals in the 2015 to 2030 time frame. To achieve these goals, Indonesia has designated a National Roadmap for Sustainable Development Goals in Presidential Regulation Number 59 of 2017. The Presidential Regulation serves as a guideline for Ministries or Agencies in National Actions Plans on Sustainable Development Goals in their respective domains. Including in the Public Procurement of Goods/Services has been fostered to increase sustainable procur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Recent surveys on SPP by Ho et al found that until 2010 studies on SPP in developing countries were relatively rare compared to research in developed countries [2]. Marita et al also corroborated this finding until the next decade, SPP research in Indonesia was relatively scarce [3]. A multi-national survey on SPP by Brammer & Walker was later accomplished [4].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Recent surveys on SPP by Ho et al found that until 2010 studies on SPP in developing countries were relatively rare compared to research in developed countries [2]. Marita et al also corroborated this finding until the next decade, SPP research in Indonesia was relatively scarce [3]. A multi-national survey on SPP by Brammer & Walker was later accomplished [4].…”
Section: Introductionmentioning
confidence: 94%
“…They affirm the previous study by Brammer & Walker [4] with extensive evidence. However, the evidence collected by Marita et al [3] in Indonesia has contested this finding. Though Indonesia has taken strategic measures by mandating e-procurement since Presidential Decree 54/2010 [3], [6], there is not much evidence of SPP until 2021 [3].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indicator is included in the Public Information Openness Index. In the electronic procurement system, the government has published the PBJP dashboard on the Electronic Procurement Service (LPSE) page [30], [31]. This policy can encourage public bodies to publish more details of PBJP transactions, expand public participation in supervision, increase the efficiency of the PBJP complaint handling mechanism, and expand the involvement of MSMEs in PBJP.…”
Section: Transparency and Participation In Procurementmentioning
confidence: 99%